PERANCANGAN VISUAL BRANDING DESA WISATA NAGREG KENDAN DI KECAMATAN NAGREG KABUPATEN BANDUNG - Ardiwinata, Fathan; Denny Nugraha, Novian; Soedewi, Sri (Telkom University, 2024)
Nagreg Kendan Village is one of the 13 tourist villages in Bandung Regency. Asa tourist village, visual branding is essential to establish its identity and unique characteristics. The issue is the lack of visual branding in Nagreg Kendan Tourist Village.This research aims to describe the design of visual branding that serves as the identity of Nagreg Kendan Tourist Village. The research method used includes qualitative methods,participatory design, observation, interviews, and documentation. The research findings from observations and interviews indicate that Nagreg Kendan Village is still in its earlystages as a tourist village. Its current visual branding is limited to a simple tourist village logo, which does not adequately represent Nagreg Kendan Village as a tourist destination.This research is expected to provide the village with an identity that will increase its recognition among the public and establish a positive brand image in the minds of tourists. Keywords: visual branding, logo, tourism village